Lost tombs of Notre Dame [videorecording (DVD)] - Tran, Florence; Le Goff, Christine; Boffey, Mercer, 1982- (PBS Distribution, 2025)
After the devastating 2019 fire at Notre Dame, two mysterious sarcophaguses were discovered under the cathedral's stone floor. Who is buried in them, and what secrets will these coffins reveal? Follow a team of archaeologists and historians as they attempt to solve centuries-old mysteries using the latest scientific investigation techniques. What can forensic analysis of the remains reveal about one of the world's most famous cathedrals and those who devoted their lives to it?